2016
DOI: 10.1039/c6lc00410e
|View full text |Cite
|
Sign up to set email alerts
|

A microfluidic device integrating dual CMOS polysilicon nanowire sensors for on-chip whole blood processing and simultaneous detection of multiple analytes

Abstract: The hemoglobin-A1c test, measuring the ratio of glycated hemoglobin (HbA1c) to hemoglobin (Hb) levels, has been a standard assay in diabetes diagnosis that removes the day-to-day glucose level variation. Currently, the HbA1c test is restricted to hospitals and central laboratories due to the laborious, time-consuming whole blood processing and bulky instruments. In this paper, we have developed a microfluidic device integrating dual CMOS polysilicon nanowire sensors (MINS) for on-chip whole blood processing an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
23
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 38 publications
(23 citation statements)
references
References 32 publications
0
23
0
Order By: Relevance
“…We then used a spectrophotometer (Nanodrop One, Thermo Fisher Scientific Inc., MA) to measure the 280-nm absorbance intensity of each dilution factor, which correlates to the total protein concentration due to three amino acids (tryptophan, phenylalanine, and tyrosine) 34 . The protein concentration and composition may vary between different clinical samples, so standard curves of each sample were constructed individually (Supplementary Fig S2 ).…”
Section: Resultsmentioning
confidence: 99%
“…We then used a spectrophotometer (Nanodrop One, Thermo Fisher Scientific Inc., MA) to measure the 280-nm absorbance intensity of each dilution factor, which correlates to the total protein concentration due to three amino acids (tryptophan, phenylalanine, and tyrosine) 34 . The protein concentration and composition may vary between different clinical samples, so standard curves of each sample were constructed individually (Supplementary Fig S2 ).…”
Section: Resultsmentioning
confidence: 99%
“…Vortex flow is induced in the microchannels of a micromachined polymethyl‐methacrylate based microfluidic device to achieve uniform sample dilution. The CMOS polysilicon nanowires are interfaced with a picoammeter to form a label‐free dynamic detection scheme without needing to contain the particles in a chamber . CMOS further enables us to integrate sensors in extremely small‐sized areas, which can easily beat the sensitivity and performance of commercially available sensors.…”
Section: Role Of Cmos In Microfluidicsmentioning
confidence: 99%
“…These DEP forces are generated by providing sinusoidal voltages to the metal electrodes through CMOS transfer gates . Kuan et al shaped an automatic real‐time fluidic control in a blood processing device using programmable microfabricated piezoelectric pumps that mixed blood sample with phosphate‐buffered saline . Chen et al and Gao et al have shown the dual use of a microheater array of microfabricated capacitive electrodes to also act as thermocapillary droplet‐propulsion actuators .…”
Section: Role Of Cmos In Microfluidicsmentioning
confidence: 99%
See 1 more Smart Citation
“…To pave the way toward POC diagnosis for cardiac disease, in this work, CMOS field-effect biosensing technology is employed for cardiac disease diagnosis with multiple biomarkers in serum. Compared with another CMOS-compatible micro-cantilever biosensing technology, CMOS field-effect biosensing technology has advantages of fabrication and integration with interface circuits and microfluidity [ 19 ].…”
Section: Introductionmentioning
confidence: 99%